2019
DOI: 10.1007/s00134-019-05583-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self-reported unacceptable outcome of intensive care treatment 1 year after discharge

Abstract: Purpose Survivors of critical illness often suffer from reduced health-related quality of life (HRQoL) due to long-term physical, cognitive, and mental health problems, also known as post-intensive care syndrome (PICS). Some intensive care unit (ICU) survivors even consider their state of health unacceptable. The aim of this study was to investigate the determinants of self-reported unacceptable outcome of ICU treatment. Methods Patients who were admitted to the ICU for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 38 publications
0
32
0
4
Order By: Relevance
“…A recent study by Heydon et al demonstrated that patients with psychological PICS related impairments identify these complaints as the most important area where they want support in [35]. Additionally, psychological PICS is referred to as the most important component of patient-reported unacceptable outcome by a recent study by Kerckhoffs et al [7]. We confirm these findings by demonstrating that PTSD and depression are both associated with a considerable decrease in quality of life and that patients with psychological PICS have a worse quality of life compared to the general Dutch population in contrast with patients without psychological PICS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Heydon et al demonstrated that patients with psychological PICS related impairments identify these complaints as the most important area where they want support in [35]. Additionally, psychological PICS is referred to as the most important component of patient-reported unacceptable outcome by a recent study by Kerckhoffs et al [7]. We confirm these findings by demonstrating that PTSD and depression are both associated with a considerable decrease in quality of life and that patients with psychological PICS have a worse quality of life compared to the general Dutch population in contrast with patients without psychological PICS.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and posttraumatic stress disorder (PTSD) related symptoms are the main components of psychological PICS. Psychological PICS is considered the most important component associated with patient-reported unacceptable outcome and decreased HRQoL [3,7]. Because these psychological sequelae can persist up to 5 years after ICU discharge, treatment of psychological PICS sequelae is becoming an important target to improve quality of life [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This can also be an effect of the research conducted in this field by these countries alongside other cultural and organisational factors. However, qualitative studies regarding the experience of patients can address decisions in daily care and can be the basis of the development of tools capable of measuring the quality of such experiences within the so‐called PROMs perspectives (patient‐reported outcome measures; Kerckhoffs et al, 2019), thus all aimed at improving the quality of care. Therefore, all countries are encouraged to consider this field as deserving investigation including international‐based research projects.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated the subjective signi cance of SF-36 score among ICU patients. A previous study showed that the mental status of PICS patients was signi cantly associated with self-reported unacceptable outcomes [50], and the underlying reason was considered to be the small sample size of the study. As indicated by the improvement in SF-36 MCS score at 6 months among all patients, there were only 18 patients with mental impairment.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%